The Roman Catholic Church and the Principle of Self-Determination: A Case Study in Mozambique - Serapião, Luís Benjamim (A journal of church and state, 1981)
Luís Benjamim Serapião; The Roman Catholic Church and the Principle of Self-Determination: A Case Study in Mozambique, Journal of Church and State, Volume 23, I